IMPROVING METHODS FOR EARLY DIAGNOSIS AND PREVENTION OF ANEMIA IN PATIENTS WITH ISCHEMIC HEART DISEASE - Gulmira I. Akhmedova (Central Asian Journal of Medicine, 2025)
In recent years, the global community has faced a pressing issue that is not only significant for the medical field but also has socio-economic implications for countries—the pandemic of chronic non-communicable diseases among the population and the resulting increase in mortality and disability. Scientific research highlights a growing incidence of ischemic heart disease and hypertension, accompanied by rising rates of disability and mortality. Anemia is a widespread condition in patients with chronic heart failure (CHF) and worsens the disease’s progression. According to studies, anemia is detected in 30–50% of patients with CHF. The development of anemia is mainly associated with iron deficiency, chronic inflammation, renal insufficiency, and decreased erythropoietin production. Clinically, anemia presents with symptoms such as fatigue, shortness of breath, tachycardia, and pale skin. Diagnosing anemia in CHF requires assessing hemoglobin, ferritin, iron levels, and renal function indicators. Treatment involves iron supplementation, the use of erythropoietin-stimulating agents, and blood transfusions when necessary. Timely diagnosis and treatment of anemia reduce the risk of complications and improve the quality of life in patients with CHF.